The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1142/s2196888822500245
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Convolutional Neural Networks for Functional and Subject Classification of Web Pages

Abstract: Information filtering and information retrieving applications are based on web page classification methods. Usually, web pages serve different functionalities or develop different topics or subjects. The diversity of web page content increases the need for automatic web page classification, making it a challenging task at the same time. Considering that the main component of the content of a web page is most often represented by the text and the classification of the text is a problem intensively studied in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“… seven studies that used a combination of HTML tag structure and text content, as shown in [10], [11], [19], [20], [24], [25], [27]  six studies that used images as shown in [9], [12]- [14], [16], [17]  three studies that used the feature of HTML tags structure as shown in [8], [15], [28]  two studies that used each feature of text content as shown in [22], [23]  two studies that used URL features as shown in [21],…”
Section: Resultsmentioning
confidence: 99%
“… seven studies that used a combination of HTML tag structure and text content, as shown in [10], [11], [19], [20], [24], [25], [27]  six studies that used images as shown in [9], [12]- [14], [16], [17]  three studies that used the feature of HTML tags structure as shown in [8], [15], [28]  two studies that used each feature of text content as shown in [22], [23]  two studies that used URL features as shown in [21],…”
Section: Resultsmentioning
confidence: 99%
“…In the same context of multi-label classification, Artene et al [51] used a CNN for multi-label multi-language classification. This study is an extension of their work in 2021 [52].…”
Section: B: Multi-label Website Classificationmentioning
confidence: 99%
“…In their first study in 2021 [52], their CNN model achieved a micro F1 score of 0.79. In their second work in 2022 [51], they divided the classification problem into two problems: functional classification and subject classification, and they increased the total dataset to 12,432 webpages to improve the results. The F1 scores for functional, subject, and all (functional + subject) were 0.88, 0.84, and 0.74, respectively.…”
Section: B: Multi-label Website Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Both types of ancient glass have been found in archaeological sites around the world, and both have been used for a variety of purposes. Ancient glass is an important part for ours to investigate the past and the way people lived in different cultures [3].…”
Section: Introductionmentioning
confidence: 99%